Field Evaluation of the InBios Chagas Detect Plus Rapid Test in Serum and Whole-Blood Specimens in Bolivia - Shah, Vishal (Clin Vaccine Immunol, 2014)
Trypanosoma cruzi causes Chagas disease, which affects an estimated 7 million to 8 million people. Chagas disease is endemic throughout Latin America, with the highest prevalence in Bolivia. Conventional diagnosis requires a well-equipped laboratory with experienced personnel. We evaluated the Chagas Detect Plus (CDP) (InBios, Seattle, WA), a rapid immunochromatographic assay for IgG antibodies to T. cruzi. CDP performance was compared to infection status based on results obtained by indirect hemagglutination assay, immunofluorescent-antibody test, and enzyme-linked immunosorbent assay. Confirmed infection required positive results by at least 2 conventional assays. We used specimens from adults of both sexes in a general hospital in the city of Santa Cruz and from pregnant women in a hospital and children in villages in the Bolivian Chaco, an area of hyperendemicity. CDP was performed in paired whole-blood and serum specimens from 385 individuals in the two hospital studies and in 200 serum specimens from the community study. CDP showed sensitivities/specificities of 96.2% (95% confidence interval, 92.7 to 98.4)/98.8% (95.9 to 99.9) in whole blood and 99.3% (97.5 to 99.9)/96.9% (94.2 to 98.6) in serum, with no differences by sex, age group, or study site. CDP showed excellent sensitivity and specificity in our study population, comparable to those of conventional serology. The test is reliable for field surveys, requires no laboratory equipment, and performed well in serum and whole blood. The CDP could also be used for accurate maternal screening to identify neonates at risk of congenital transmission. CDP performance data in diverse geographic areas are needed to strengthen the evidence base for its use.